2008
DOI: 10.1016/j.forsciint.2008.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Exact solutions to Bayesian and maximum likelihood problems in facial identification when population and error distributions are known

Abstract: The reliability of traditional photogrammetric identification techniques using a small number of facial landmarks has recently come in for criticism. However, the transformation of parameters into a new face space in which the error distributions are orthogonal, yields a maximum likelihood solution to the problem of identifying a photographed face from a small, known, population which, in a simulated example, raises the success rate from 20% to 93%. A full transformation yielding simultaneously independent pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Alternative databases would be necessary if the system was to be applied to those of a different ethnicity, age group or gender. It may also be possible to apply alternative novel statistical techniques [35]. Furthermore, Yoshino and colleagues [24] have suggested that a database of 3D images, and associated facial measurements could be routinely obtained in a similar manner to police mug-shots.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative databases would be necessary if the system was to be applied to those of a different ethnicity, age group or gender. It may also be possible to apply alternative novel statistical techniques [35]. Furthermore, Yoshino and colleagues [24] have suggested that a database of 3D images, and associated facial measurements could be routinely obtained in a similar manner to police mug-shots.…”
Section: Discussionmentioning
confidence: 99%
“…Mock witnesses are used to assess the fairness of eyewitness lineups (Doob & Kirshenbaum, ; McQuiston & Malpass, ). Likewise, a mock witness filler‐control test could be conducted to provide evidence about whether the defendant does or does not match the culprit (see Allen, , for a description of a method of identification based on facial landmarks).…”
Section: Introductionmentioning
confidence: 99%
“…A abordagem fotoantropométrica tradicional envolve a identificação de um número de pontos anatômicos na imagem e a medição das distâncias entre eles (ALLEN, 2008;MORETON;MORLEY, 2011). Para que proporções, índices e ângulos sejam mensurados, ao invés de se utilizar medidas lineares, pode-se normatizar estas distâncias, dividindo-as pela distância interpupilar, por exemplo.…”
Section: Fotoantropometria: a Imagem Como Fonte De Informaçãounclassified